Climate change in the EU's macroeconomic imbalance procedure - Wolf-Fabian Hungerland; Christoph Altmeppen (Intereconomics, 2024)
EU member states observe an elaborate process to preserve macroeconomic stability: the macroeconomic imbalance procedure (MIP). The MIP is supposed to monitor and prevent macroeconomic imbalances - and if necessary, correct them. It considers a variety of variables to determine the existence of imbalances, e.g. the current account balance or unit labour costs. However, the macroeconomic impact of climate change is ignored. In light of the growing economic risks due to climate change, this article argues that the MIP should consider climate-related risks explicitly to maintain relevance.
Keywords: E61; E62; 330